Teaching Practice is not Enough for EFL Teachers: Voices from IAIN Surakarta - Imroatus Solikhah; Teguh Budiharso (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
This study explores teaching practices for English Language Education program of IAIN Surakarta were implemented to link the gaps between theory and actual needs at schools. Relying on the qualitative approach, this study used content analysis as the main data sources, observation and interview to collect data. The results of the study show that teaching practice for the ELT in IAIN Surakarta indicate restrictions. With overall duration of 16 weeks, teaching practices at IAIN Surakarta is set in 6 credits, each of which consists of (1) micro teaching (2 credits), (2) administrative observation, (3) classroom observation, (4) classroom teaching practices. During the field practices, complaints from mentor teachers appear that practican students are not well prepared in teaching skills and limited knowledge is performed to English competence performance in the classroom. Students claim that preparation in the itinerary of teaching practice they received from campus are not definitely sufficient as too many administrative processes are emphazised and mentoring system does not suffice to equip teaching skills